OpenStreetMap, the Wikipedia Map - Gunther Maier (REGION, 2014)
This paper presents OpenStreetMap and closely related software as a resource for spatial economic research. The paper demonstrates how information can be extracted from OpenStreetMap, how it can be used as a geographical interface in web-based communication, and illustrates the value of the tools by use of a specific application, the WU campus GIS.
Keywords: 330; electronic mapping; GIS; OpenStreetMap; OpenLayers; computer sciences